2008
DOI: 10.1371/journal.pntd.0000240
|View full text |Cite
|
Sign up to set email alerts
|

Altered Patterns of Gene Expression Underlying the Enhanced Immunogenicity of Radiation-Attenuated Schistosomes

Abstract: BackgroundSchistosome cercariae only elicit high levels of protective immunity against a challenge infection if they are optimally attenuated by exposure to ionising radiation that truncates their migration in the lungs. However, the underlying molecular mechanisms responsible for the altered phenotype of the irradiated parasite that primes for protection have yet to be identified.Methodology/Principal FindingsWe have used a custom microarray comprising probes derived from lung-stage parasites to compare patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…changes and responses associated with this effective vaccination strategy have been highlighted as a useful research direction for the future [52]. The effects on gene expression that radiation attenuation has on the parasite itself have been the focus of a recent microarray study [53].…”
Section: Attenuated Cercariaementioning
confidence: 99%
See 1 more Smart Citation
“…changes and responses associated with this effective vaccination strategy have been highlighted as a useful research direction for the future [52]. The effects on gene expression that radiation attenuation has on the parasite itself have been the focus of a recent microarray study [53].…”
Section: Attenuated Cercariaementioning
confidence: 99%
“…Dillon and colleagues used a focused S. mansoni microarray platform based primarily on sequences from "lung schistosomula" [25], to investigate the gene transcription in radiation attenuated parasites [53]. In vitro maintained mechanically derived schistosomula were subjected to microarray analysis and compared to controls that were not radiation attenuated.…”
Section: Attenuated Cercariaementioning
confidence: 99%
“…It was shown that infection of humans with live, RA parasites led to strong protection against subsequent challenge infections with normal cercariae (Correa-Oliveira et al, 2000;Ribeiro de Jesus et al, 2000). Vaccination of animal models with RA cercariae has thus led to an adult worm burden reduction in experimental schistosomiasis of 60-70% (Bickle et al, 1979a,b; CauladaBenedetti et al, 1991;Coulson et al, 1998;McManus, 1999;Dillon et al, 2008). The molecular mechanism of protection with RA is unclear; however, the immune response appears to result from transcriptional suppression in the attenuated parasites during the early stage of development (Dillon et al, 2008).…”
mentioning
confidence: 99%
“…Vaccination of animal models with RA cercariae has thus led to an adult worm burden reduction in experimental schistosomiasis of 60-70% (Bickle et al, 1979a,b; CauladaBenedetti et al, 1991;Coulson et al, 1998;McManus, 1999;Dillon et al, 2008). The molecular mechanism of protection with RA is unclear; however, the immune response appears to result from transcriptional suppression in the attenuated parasites during the early stage of development (Dillon et al, 2008). Transcriptional suppression in RA was observed for a variety of genes including those encoding tegument proteins, members of signalling pathways associated with GPCRs, neurotransmitters and cytoskeletal components.…”
mentioning
confidence: 99%
“…Secondly, and more likely, the exposure of SmTSP-2 on the apical membrane may be a stage-specific phenomenon and a feature of the transition of the parasite from a free-living cercaria to the parasitic schistosomula stage. This transformation seems to be the phase that is vulnerable to immune attack by the host (Dillon et al, 2008; Chapter 3Characterisation of Schistosoma mansoni DLCs and TALs in the parasite life cycle …”
mentioning
confidence: 99%